Kidney Transplant and Dialysis Patients Remain at Increased Risk for Succumbing to COVID-19. Issue 5 (22nd April 2023) - Weiss, Anne; Hendrickx, Rodinde; Stensgaard, Eva; Jellingsø, Mads; Sommer, Morten O.A.
Abstract : Background: Immunocompromised patients have been at an increased risk of succumbing to coronavirus disease 2019 (COVID-19) since the beginning of the pandemic. Methods: Here, we analyzed mortality and case fatality data from dialysis and kidney transplant patients, and compared each with an age-matched subgroup of the general population. Results: We found that both patients on dialysis and kidney transplant patients remain at increased risk of succumbing to COVID-19 despite all available countermeasures. Conclusions: The analyses underline the need for additional protection for this vulnerable population.